Another mite species discovered via social media - Ameronothrus retweet sp. nov. (Acari, Oribatida) from Japanese coasts, exhibiting an interesting sexual dimorphism. Issue 4 (4th July 2022) - Pfingstl, Tobias; Hiruta, Shimpei F.; Bardel-Kahr, Iris; Obae, Yuito; Shimano, Satoshi
ABSTRACT: The recent discovery of the oribatid mite Ameronothrus twitter via a social media platform resulted in a considerable media response and raised the awareness of the public for these tiny organisms. As a direct consequence, another new marine associated ameronothroid species was now discovered via the same social media service. Moreover, the record of this new species, Ameronothrus retweet sp. n., represents the first report of an ameronothroid taxon from the Sea of Japan coast, indicating that this coastline was successfully colonized by these organisms and that further species could be present there. Ameronothrus retweet sp. n. shows an extraordinary sexual dimorphism with females having relatively shorter legs and a strongly folded notogastral integument. Based on morphological characteristics, it is suggested that the new species is closest related to Ameronothrus lineatus and Ameronothrus nigrofemoratus . A molecular genetic investigation of selected ameronothroid taxa, using the 18S rRNA gene, shows that all Ameronothrus species are closely related and represent a distinct monophyletic genus. In a larger phylogenetic context, the Fortuyniidae and Selenoribatidae are given as sister taxa with a monophyletic origin, whereas certain members of Ameronothridae are placed in paraphyletic positions, supporting theories of an independent origin of the marine associated lifestyle in ameronothroid mites. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D0D9B80E-D144-436D-82B1-F2847178E861 http://www.zoobank.org/urn:lsid:zoobank.org:act:0CFB4401-1EC4-4BB8-97CD-13812FF11D83